1998
DOI: 10.1023/a:1005756023082
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Peripheral nervous system alterations were induced in adult rats by administration of cisplatin (CDDP) 2 mg/kg twice weekly for 4.5 weeks. Dorsal root ganglion neurons showed pathological changes. Morphometric determinations demonstrated a reduction in size of the somatic, nuclear and nucleolar area. The nucleoli were the most involved subcellular structures. Nerve conduction velocity and the tail-flick test for pain were both significantly altered in CDDP treated rats, whereas the rota-rod test for coordinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
3

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(11 citation statements)
references
References 46 publications
1
7
0
3
Order By: Relevance
“…Consistent with earlier clinical (Cooley et al, 1994; Sleijfer et al, 1985) and experimental (Tredici et al, 1998; Joseph and Levine, 2009; Ta et al, 2009) reports, mechanical and heat hyperalgesia occurred in the majority of mice treated with cisplatin in the present study. Because cisplatin does not cross the blood-brain barrier (Gregg et al, 1992) and no obvious deterioration in general health or motor activity occurred during the 7-day course of treatment, the hyperalgesia observed in cisplatin-treated mice is most likely due to changes in sensory neurons.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with earlier clinical (Cooley et al, 1994; Sleijfer et al, 1985) and experimental (Tredici et al, 1998; Joseph and Levine, 2009; Ta et al, 2009) reports, mechanical and heat hyperalgesia occurred in the majority of mice treated with cisplatin in the present study. Because cisplatin does not cross the blood-brain barrier (Gregg et al, 1992) and no obvious deterioration in general health or motor activity occurred during the 7-day course of treatment, the hyperalgesia observed in cisplatin-treated mice is most likely due to changes in sensory neurons.…”
Section: Discussionsupporting
confidence: 93%
“…Antidromic tail-nerve conduction velocity was assessed by using a Myto EBNeuro electromiograph (EBNeuro, Firenze, Italy), as described (24). The latency of potential recorded in the two sites after nerve stimulation (stimulus duration, 100 msec; filter, 1 Hz to Ϫ5 MHz) was determined (peak to peak), and NCV was calculated accordingly.…”
Section: Methodsmentioning
confidence: 99%
“…The latency to lick a hind paw was measured. The mice were removed from the plate immediately upon licking a hind paw or if no response occurred within 50 s. At the same time, the rotarod test was employed to assess peripheral motor nerve toxicity [33,34]. The mice were trained to remain on the rotarod apparatus (YLS-4C, ZS Dichuang Inst, Peking, China) before the experimental data were obtained.…”
Section: Peripheral Neurotoxicitymentioning
confidence: 99%
“…These results indicated that cisplatin significantly injured the sensory nerve, whereas Δ-Ru1 showed no toxicity toward it. The rotarod test was used to evaluate coordination, which if altered, could indicate peripheral motor neurotoxicity [33]. In the rotarod test, the time that the animal spent on the rotating drum was measured (Fig.…”
Section: Peripheral Neurotoxicitymentioning
confidence: 99%